The Role Of Public Policy In Addressing Global Poverty And Inequality: Case Studies In Developing Countries - Syamsiyah Adilah Daulay; Timbul Dompak (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2025)
Poverty and economic inequality pose substantial issues for numerous emerging nations, with an estimated 712 million individuals globally residing in extreme poverty as of 2022. This article analyzes the impact of public policy on these concerns, with case studies from Indonesia, Brazil, and India. This research employs literature review methodologies to analyze several implemented policies, including conditional cash assistance, enhanced access to education, health services, infrastructure development, and economic empowerment initiatives. Conditional cash transfer programs, exemplified by Indonesia's Family Hope Program and Brazil's Bolsa Familia, have demonstrated efficacy in enhancing access to fundamental services for impoverished populations. Conversely, implementation obstacles, including limited institutional capacity and inadequate oversight, frequently obstruct policy achievement in underdeveloped nations. This study concludes that effective public policy necessitates a multifaceted strategy involving resource redistribution, the creation of economic possibilities, and enhanced access to education and healthcare. This research aims to offer insights for other developing nations by examining the policies enacted in these three countries, so facilitating the creation of more inclusive and sustainable public policy interventions. These findings underscore the significance of the government's involvement in empowering impoverished communities through systematic and sustainable measures to foster equitable development and mitigate inequality.